Case of autoimmune polyglandular syndrome type 2: how we uncovered the diagnosis. Issue 2 (26th February 2019) - Arya P V, Akhila; Kumar, Jayesh; Unnikrishnan, Dileep; Raj, Rishi
Abstract : A 24-year-old man with no significant medical history presented to the medical clinic with vomiting and giddiness for 2 days, loss of appetite for 1 month and progressive fatigability for the preceding 4 months. On examination, he was found to be hypotensive and was admitted to the hospital for work-up. Considering his abnormal labs and physical findings, he was worked up and was diagnosed with primary adrenal insufficiency. On further work-up for the aetiology of his Addison's disease, he was found to have concurrent autoimmune thyroiditis and vitiligo. A final diagnosis of autoimmune polyglandular syndrome type 2 was made. The patient was started on hormone replacement therapy and reported improvement of symptoms on 3-month follow-up visit.